Continuous Response Monitoring of Relative Time-to-Contact Judgments: Does Effective Information Change During an Approach Event?. Issue 1 (2nd January 2016) - DeLucia, Patricia R.; Meza-Arroyo, Manuel; Baurès, Robin; Ranjit, Manish; Hsiang, Simon; Gorman, Jamie C.
ABSTRACT: In many previous studies of time-to-contact (TTC) judgments of approaching objects, a response was measured after observers viewed the entire event and was used to infer the informational basis for the judgment. Such measures primarily reflect the information used at the end of the approach event and may not reveal whether observers used different information at different times during the event. Evidence indicates that observers use multiple information sources and that the effectiveness of information varies with distance. We introduce a method in which observers continuously report which of 2 approaching objects would reach them first, throughout the approach. We identified the occurrence and time of response reversals. Most observers changed their relative TTC judgments during the event. The pattern of responses indicated that observers did not use tau early during the approach when objects were far and did not use optical size later when the objects were closer. Most observers relied on either optical size or optical expansion rate early during the approach and expansion rate later during the event, although there were individual differences. A single relative TTC judgment measured after observers view an approach event may not reflect judgments or their informational basis throughout the entire event.